Anthropology and Geopolitics of the Homo Laïcus - Sibertin-Blanc, Guillaume (Political theology, 2021)
This text addresses the condition of the current reversal of the liberal and anti-discriminatory principles of laïcité which led to their repressive application: a “meta-laicism,” similar to the associated meta-racism. Rather than exploring laïcité as a tool to manipulate for tactical advantage, which is only a part of the problem, – we are examining this reversal from the historical and political conditions of a secular material constitution, its uneven development which characterizes its historical synthesis, and the resulting effects of the crisis of its hegemony. The looming outcome of this reversal is not only hypothetical, but hyperbolical in two ways. Indeed, it calls for an increase of egalitarian and emancipatory struggles based on a no less necessary increase of political liberalism. This would allow the acceptance of the recognition of the legitimate ideological forces of Islamic cultures in the field of ideological and political confrontations.